The Effects of Income and Consumption Tax Regimes and Future Tax Rate Uncertainty on Proportional Savings and Risk-Taking. - Meade, Janet A. (The Accounting Review, 1995)
Presents an experimental design examining the effect of income and consumption tax regimes and future tax rate on proportional savings and risk-taking. Results indicating that income tax regime reduces proportional savings and increase proportional risk-taking when compared to a consumption tax regime.